2007
DOI: 10.1007/s11695-007-9005-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Ultrasonographic Examination for Nonalcoholic Steatohepatitis in Morbidly Obese Patients Undergoing Laparoscopic Bariatric Surgery

Abstract: FS and MFS on US examination exhibit acceptable sensitivity and high specificity for the detection of the presence of NASH in morbidly obese patients and may aid in the selection of patients for closer follow-up or liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
(29 reference statements)
5
34
1
3
Order By: Relevance
“…In addition, levels of liver transaminases do not always reflect the degree of inflammation. However, there are clear evidences that a score of 2 or more corresponded to steatohepatitis [4,10]. Moreover, as demonstrated in the study, in grade 3 hepatosteatosis group, AFP level elevation is more striking than in the other groups, suggesting that AFP level is well correlated with the disease severity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, levels of liver transaminases do not always reflect the degree of inflammation. However, there are clear evidences that a score of 2 or more corresponded to steatohepatitis [4,10]. Moreover, as demonstrated in the study, in grade 3 hepatosteatosis group, AFP level elevation is more striking than in the other groups, suggesting that AFP level is well correlated with the disease severity.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have demonstrated that the sensitivity, specificity, and positive predictive value of this technique to detect steatosis is as high as 80-100% [4,10,11]. However, there are several limitations as well, including operator dependency, less sensitivity in obese patients, and inability to diagnose steatohepatitis and hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 mRNA did not differ significantly between groups (14.46 (8.70) and 14.70 (11.87) arbitrary units in the low and the high HOMA-IR groups, respectively). As increased expression and activity of FOXO1 has been associated with NASH 30 and NASH is strongly related to the steatosis score in obese subjects, 31 we determined the relation of hepatic FOXO1 mRNA with steatosis score. Although average values (s.d.)…”
Section: Resultsmentioning
confidence: 99%
“…29 These contrasting results may be reconciled by an association of ADIPOR1/2 mRNA levels with IR as observed in our study. As NASH is strongly related to the steatosis score in obese subjects as ascertained by ultrasound, 31 our analyses adjusting for steatosis grade and plasma ferritin would be expected to reduce potential confounding by NASH.…”
Section: Discussionmentioning
confidence: 99%
“…): healthy liver, <2%; mild HS, ≥2% to 5%; moderate HS, ≥5% to 10%; and severe HS, ≥10% [12] . According to the fat classes, the following four widely accepted items were used for image analysis to establish standards for fatty liver grade of sheep [13,14] : echogenicity of liver parenchyma (bright liver) compared with the echogenicity of the renal cortex (L-K contrast), visualization of intrahepatic vessels (vessels blurring), and visualization of the posterior hepatic lobe, including the diaphragm, postcaval vein, rumen, and intestines. Visualization of these image characteristics were classified as absent, slight, intermediate, and marked.…”
Section: Imaging Analysismentioning
confidence: 99%